The Concept of Tazkiyah Al-Nafs in the Qur'an and its Implications for Human Moral-Spiritual Growth (Hermenutical Study by Fazlur Rahman) - Siti Mukarromatussa’diyyah; Nyoko Adi Kuswoyo; Miftara Ainul Mufid; Ahmad Zainuddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the concept of tazkiyah al-nafs in the Qur’an and its implications for human moral and spiritual development. In response to contemporary moral and spiritual crises, this research aims to provide a contextual understanding of soul purification as a foundation for ethical character building. This study employs a qualitative approach through library research, analyzing Qur’anic verses using Fazlur Rahman’s hermeneutical framework, particularly the double movement method, which involves examining the historical context of revelation and deriving universal moral principles applicable to modern life. The findings reveal that tazkiyah al-nafs is not merely a process of spiritual purification but also a transformative framework that shapes self-control, ethical awareness, and moral responsibility in both individual and social contexts. Furthermore, the study highlights that the values embedded in tazkiyah al-nafs such as honesty, self-discipline, and social responsibility remain highly relevant in addressing contemporary ethical challenges. Therefore, this concept serves as a significant ethical and spiritual foundation for fostering a morally conscious and spiritually aware society.